VALIDASI TERHADAP KELAYAKAN PRODUK VIRTUAL LABORATORIUM PADA PEMBELAJARAN PRAKTIKUM MATERI PENCEMARAN AIR - Elvira Destiansari; Susy Amizera; Zainal Arifin (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2021)
This study aims to explain the results of the validation of the feasibility of virtual laboratory products in practicing water pollution materials. This research is a descriptive research and is also part of the development of a virtual laboratory on water pollution which consists of a preliminary study stage, a research planning stage and a product development stage. In this study, the data used were data at the develop preliminary product stage, namely product validation data. The results of material validation include 80.00% (sufficient) in the first validation and 88.57% (valid) in the second validation. The results of display validation include 77.14% (sufficient) in the first validation, 80.00% (sufficient) in the second validation, and 94.28% (valid) in the third validation. The results of language validation include 80.00% (sufficient) in the first validation and 93.33% (valid) in the second validation. Based on these results, the results of virtual lab development on water pollution material based on the results of material validation, appearance, and language constructs by a team of experts are categorized as valid and can be used for further processing.